(untitled) (Semiárida, 2025)
The use of plant growth-promoting microorganisms in rainfed cropping systems is an agronomic strategy aimed at alleviating abiotic stress and enhancing crop performance. However, evidence on their effectiveness under variable environmental conditions in semi-arid regions remains limited. This study evaluated the impact of seed inoculation with Azospirillum argentinense Az39 on yield components and grain production in wheat (Triticum aestivum L.) grown under representative conditions of the central semi-arid Pampas. Field trials were conducted over three consecutive growing seasons (2020–2022) at seven locations characterized by Entic and Petrocalcic Haplustolls. On average, inoculated treatments achieved an 8.9 % increase in grain yield compared to the non-inoculated control. Yield gains were primarily associated with increased grain number and grain filling, particularly in seasons with moderate water limitations during early crop development. These results support the potential of A. argentinense Az39 as a biological input to improve wheat productivity under dryland farming conditions in semi-arid environments.